Analisis Teaching Factory terhadap Kompetensi Pendidikan Kewirausahaan Peserta Didik SMK Melalui Pendekatan SLR (Systematic Literature Review) - Fitriawati, Rega; Lutfiatul Jannah, Nur; Dian Rahmawati, Imelda (EduInovasi: Journal of Basic Educational Studies, 2025)
This entrepreneurship education is an education that's beginning to exist in the era of globalization 5.0. Almost all elements of society, especially in schools, are beginning to implement and prioritize entrepreneurship education. Teaching factory is a method of entrepreneurship education that focuses on production or services to improve work readiness, apply skills, and foster work ethic in vocational graduates. The purpose of this study is to analyze the teaching factory on the entrepreneurship education competence of vocational students. This research uses a systematic literature review (SLR) methodology that collects and analyzes relevant research journals according to the research steps. The results of this study indicate that teaching factory, as a production-based learning method, has the ability to align instruction with industrial practice so that students not only master technical skills, but also develop the management, interpersonal, and creative thinking skills needed to become successful entrepreneurs. The research also identified some challenges to the implementation of the teaching factory, such as a lack of management support, limited facilities, and the need for more effective partnerships with industry, requiring strong collaboration between schools, industry, and government. Teaching factory has significant potential in improving the entrepreneurship education competencies of vocational students.